Effect of inhalant allergies on voice quality in women - Bonetti, Ana (Array, 2018)
Reports of negative influence of inhalant allergies on voice quality in the world are increasingly frequent. In order to evaluate this impact using objective and subjective methods, women with allergies (n = 30) and women without allergies (n= 30) underwent multidimensional assessment consisting of perceptual assessment, Voice Handicap Index – HR (Bonetti and Bonetti, 2013) and acoustic analysis. The results indicate a negative effect of allergies on voice quality, which is measurable as significantly worse VHI-HR results and worse harmonics-to-noise ratio (HNR) in acoustic analysis.